The Great Green Wall: An overview and lessons learnt - Marie Ladekjær Gravesen; Mikkel Funder (Danish Institute for International Studies (DIIS), 2022)
This DIIS Working Paper provides a broad overview of the Great Green Wall initiative to draw out lessons learnt from the first half of the programme. Overall, the authors find it unrealistic for the Great Green Wall to significantly alter root causes of migration and conflict in the Sahel region and the programme cannot be considered a nature-based solution (NbS) in its entirety. However, the paper recommends wider use of the International Union for Conservation of Nature (IUCN) criteria for NbS in the Great Green Wall's subprojects. This would ensure inclusion of stakeholders and expand consideration to rights and access when changes in tenure are implemented as part of tree planting. Collaboration with national level organisations, who understand contextualised livelihood vulnerabilities, is also recommended. Moreover, overall support to the GGW through the Global Environment Facility, the Green Climate Fund etc. should promote improved coordination of activities and consistent monitoring across partner countries and subprojects. More qualitative analyses of project site contexts should also be included among monitoring tools.
Keywords: 330; Natural resources and environment; Food and agriculture; Land rights and investments; Climate change and environment; Migration and development; Development policy; Inequality and poverty; Development in practice; Conflict and economy